The global food price crisis threatens to cause a global nutrition crisis: New evidence from 1.27 million young children on the effects of inflation - Headey, Derek D.; Ruel, Marie T. (International Food Policy Research Institute, 2023)
Frequent food crises with spiking prices have become the new normal in the 21st century, bringing urgency to the task of understanding their nutritional impacts on poor and food insecure populations. In a new analysis of 1.27 million children in 44 low- and middle-income countries (LMICs), we show that exposure to food inflation in the womb and first years of life is associated with greater risks of child wasting in the short run and stunting in the long run. Food inflation also poses larger wasting risks for children of poor and landless rural households, exacerbating existing inequalities. These results show the urgency of policies focused on improving maternal and young child nutrition, and the importance of broadening actions to reduce food price volatility and boost access to nutritious foods.